Work Motivation of Teachers at Wat Tri Samakkee School under the Samut Prakan Primary Educational Service Area Office 1 - เทียนสว่างชัย อรรถฎากร; วงษ์เล็ก ภูษิตย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to examine and compare the level of work motivation of teachers at Wat Tri Samakkee School under the Samut Prakan Primary Educational Service Area Office 1, classified by teachers’ personal factors. The population consisted of 38 teachers at Wat Tri Samakkee School. The research instrument was a questionnaire with an Index of Item–Objective Congruence (IOC) ranging from 0.67 to 1.00 and an overall reliability coefficient of 0.86. The data were analyzed using percentage, mean (μ), and standard deviation (σ), and the hypotheses were tested through mean comparison. The findings revealed that 1) the overall level of teachers’ work motivation was at a high level. When considered by aspects, two aspects were at a high level and one aspect was at a moderate level. The aspect with the highest mean was the need for achievement, followed by the need for affiliation and the need for power, respectively.2) teachers with different personal factors, including gender, age, educational level, income, and work experience, showed no statistically significant differences in overall work motivation.